A neotype for Pontoscolex corethrurus (Müller, 1857) (Clitellata) - James, Samuel W.; Bartz, Marie L.c.; Stanton, David W. G.; Conrado, Ana C.; Dupont, Lise; Taheri, Shabnam; Silva, Elodie Da; Cunha, Luís; Brown, George G. (Zootaxa, 2019)
Following many decades of work on the taxonomy, biology and ecology of the globally-distributed tropical earthworm Pontoscolex corethrurus (Müller, 1857), morphological and molecular data have shown that the stability and effectiveness of nomenclature depends on the designation of a neotype from the type locality. We do that, with all the required justifications, and provide sufficient information to permit the correct identification of this species.